Swept-Tone Stimulus-Frequency Otoacoustic Emissions in Human Newborns - Abdala, Carolina (Trends Hear, 2019)
Several types of otoacoustic emissions have been characterized in newborns to study the maturational status of the cochlea at birth and to develop effective tests of hearing. The stimulus-frequency otoacoustic emission (SFOAE), a reflection-type emission elicited with a single low-level pure tone, is the least studied of these emissions and has not been comprehensively characterized in human newborns. The SFOAE has been linked to cochlear tuning and is sensitive to disruptions in cochlear gain (i.e., hearing loss) in adult subjects. In this study, we characterize SFOAEs evoked with rapidly sweeping tones in human neonates and consider the implications of our findings for human cochlear maturation. SFOAEs were measured in 29 term newborns within 72 hr of birth using swept tones presented at 2 oct/s across a four-octave frequency range (0.5–8 kHz); 20 normal-hearing young adults served as a control group. The prevalence of SFOAEs in newborns was as high as 90% (depending on how response “presence” was defined). Evidence of probe-tip leakage and abnormal ear-canal energy reflectance was observed in those ears with absent or unmeasurable SFOAEs. Results in the group of newborns with present stimulus-frequency emissions indicate that neonatal swept-tone SFOAEs are adult-like in morphology but have slightly higher amplitude compared with adults and longer SFOAE group delays. The origin of these nonadult-like features is probably mixed, including contributions from both conductive (ear canal and middle ear) and cochlear immaturities.